Find the Laplace transforms of
1.(t^2 e^2t)
2.[1+e^(-t)]^3
3. [t√(1+sin t)]
1. "f(t)=t^2e^{2t}"
"=\\dfrac{1}{2-s}t^2e^{(2-s)t}-\\dfrac{2}{(2-s)^2}te^{(2-s)t}+"
"+\\dfrac{2}{(2-s)^2}\\int e^{(2-s)t}dt=\\dfrac{t^2}{2-s}e^{(2-s)t}-"
"-\\dfrac{2t}{(2-s)^2}e^{(2-s)t}+\\dfrac{2}{(2-s)^3}e^{(2-s)t}+C"
"F(s)=\\displaystyle\\int_{0}^\\infin e^{-ts}t^2e^{2t}dt="
"=\\lim\\limits_{b\\to\\infin}\\bigg[-\\dfrac{t^2e^{(s-2)t}}{s-2}-\\dfrac{2te^{(s-2)t}}{(s-2)^2}-\\dfrac{2e^{(s-2)t}}{(s-2)^3}\\bigg]\\begin{matrix}\n b \\\\\n 0\n\\end{matrix}="
"=-0-0-0+0+0+\\dfrac{2}{(s-2)^3}=\\dfrac{2}{(s-2)^3}, s\\not=2"
"L(t^2e^{2t})=\\dfrac{2}{(s-2)^3}, s\\not=2"
2. "f(t)=(1+e^{-t})^3=1+3e^{-t}+3e^{-2t}+e^{-3t}"
"F(s)=\\displaystyle\\int_{0}^\\infin e^{-ts}(1+3e^{-t}+3e^{-2t}+e^{-3t})dt=""=\\displaystyle\\int_{0}^\\infin (e^{-ts}+3e^{-(s+1)t}+3e^{-(s+2)t}+e^{-(s+3)t})dt="
"=-0-0-0-0+\\dfrac{1}{s}+\\dfrac{3}{s+1}+\\dfrac{3}{s+2}+\\dfrac{1}{s+3}"
"L((1+e^{-t})^3)=\\dfrac{1}{s}+\\dfrac{3}{s+1}+\\dfrac{3}{s+2}+\\dfrac{1}{s+3},"
"s\\not=-3, s\\not=-2, s\\not=-1, s\\not=0"
3.
"f(t)=t\\sqrt{1+\\sin{t}}="
"=t\\sqrt{\\sin^2{(t\/2)}+2\\sin{(t\/2)}\\cos{(t\/2)}+\\cos^2{(t\/2)}}="
"=t|\\sin{(t\/2)}+\\cos{(t\/2)}|"
Let "\\sin{(t\/2)}+\\cos{(t\/2)}\\geq0." Then
"f(t)=t(\\sin{(t\/2)}+\\cos{(t\/2)})"
"L(\\sin{(t\/2)}+\\cos{(t\/2)})=L(\\sin{(t\/2)})+L(\\cos{(t\/2)})="
"=\\dfrac{\\dfrac{1}{2}}{s^2+\\dfrac{1}{4}}+\\dfrac{s}{s^2+\\dfrac{1}{4}}"
By multiplication by "t" property
"L(t(\\sin{(t\/2)}+\\cos{(t\/2)}))=-1\\dfrac{d}{ds}\\bigg(\\dfrac{\\dfrac{1}{2}+s}{s^2+\\dfrac{1}{4}}\\bigg)="
"=-\\dfrac{s^2+\\dfrac{1}{4}-s-2s^2}{(s^2+\\dfrac{1}{4})^2}="
"=\\dfrac{s^2+s-\\dfrac{1}{4}}{(s^2+\\dfrac{1}{4})^2}=\\dfrac{4(4s^2+4s-1)}{(4s^2+1)^2}"
"L(t\\sqrt{1+\\sin{t}})=\\dfrac{4(4s^2+4s-1)}{(4s^2+1)^2}"
Comments
Leave a comment